Teachers' Perceptions of Independent Learning in the Merdeka Curriculum: A Phenomenological Study - Renny Nur Afida; Haryono; Titi Prihatin (Journal of Education Technology, 2024)
This research is motivated by the gap between the accepted and practised Merdeka Belajar policies in the field. Based on data released by the Ministry of Education, Culture, Research and Technology, around 60% of teachers are still limited in mastering technology. Only 40% of teachers can learn the Merdeka Curriculum without experiencing obstacles. This has impacted the variation and readiness of all stakeholders in its operationalization in educational units. This study aims to understand teachers' perceptions as the spearhead of curriculum actors at the operational level regarding the meaning of Merdeka Learning. This study uses a qualitative approach with a phenomenological method, which is analyzed using Interpretative Phenomenological Analysis with the help of the ATLAS.ti application. The study results show similarities and differences in perceptions between driving and non-driving teachers regarding the understanding of the concept of Merdeka Learning, its relationship to implementation and challenges. Driving teachers understand this concept better by sharing knowledge with fellow teachers and receiving support from driving schools as pioneers in implementing the Merdeka Curriculum. In contrast, non-driving teachers try to follow the flow by learning through other platforms, such as social media. Challenges in implementing the Independent Curriculum involve support from all stakeholders and the diversity of student characters that give rise to response variations. Differences in perception between driving and non-driving teachers regarding the concept of the Independent Curriculum affect its implementation. This study can enrich the existing literature by adding new perspectives or relevant empirical findings.